ENHANCEMENT SOLUBILITY AND DISSOLUTION RATE OF PARACETAMOL AND IBUPROFEN BY COAMORPHOUS PARTICLES USING MICROWAVE TECHNIQUE: ENHANCEMENT SOLUBILITY AND DISSOLUTION RATE - ANILKUMAR SHINDE; NAMDEO JADHAV; OJAS SHINDE; PRAVIN PATIL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to the preparation of a coamorphous (COAM) system of paracetamol (PA) (Biopharmaceutics Classification System [BCS] Class-III) and ibuprofen (IB) (BCS Class-II) for enhancement of solubility and dissolution of IB. Methods: The COAM system was prepared by chemical electric magnetic field microwave-assisted method. Several batches with different concentrations of COAM PA and IB were prepared at constant temperature, pressure, and holding time. Solubility studies were carried out in different pH condition and the batch, which show the highest increase in solubility 98.00%. COAM samples were characterized by solubility, dissolution, Fourier transform infrared (FTIR), X-ray diffraction (XRD), and differential scanning calorimetry (DSC) studies. Results: FTIR results showed evidence of molecular interactions between both the drugs. Maximum increase in aqueous solubility of IB was seen 500:200 mg dose ratio (COAM) batch E in phosphate buffer 7.4. The COAM system increased solubility of IB about 98.70%. The solubility and dissolution rate of IB were also enhanced. In vitro drug release study, 100% of the drug was released within 120 min. Thus, saturation solubility and dissolution rate of IB were found significant improved unlike PA. XRD and DSC results confirmed amorphization of IB. FTIR results evidenced hydrogen bonding interactions between both the drugs. In accelerated stability studies, powder XRD and DSC results demonstrated insignificant changes, thus confirming successful stabilization of IB by PA. Conclusion: Hence, it concluded that the study of COAM of PA and IB successfully prepared by microwave-assisted method to enhance solubility, dissolution, stability, and bioavailability.